Affective Consequences of Social Comparisons by Women With Breast Cancer: An Experiment - Corcoran, Katja; Kedia, Gayannee; Illemann, Rifeta; Innerhofer, Helga (Frontiers in Psychology, 2020)
Objective: People with a severe illness often meet and compare themselves with other patients. Some of these comparison standards do well, others do poorly. Such comparisons could have positive as well as negative consequences depending on whether people identify or contrast from the standard. In the present study, we examine whether patients with breast cancer can benefit from comparisons by engaging in favourable comparison processes. Design: 102 women diagnosed with breast cancer were randomly assigned to read a (fictitious) self-report from a well or poorly-adjusted breast cancer patient. Main Outcome Measures: Participants reported their affective reaction (mood, anxiety, depression) and specified their comparison process (identification or contrast). Results: In general, participants engaged in favourable comparison processes by contrasting predominantly with poorly-adjusted patients, and identifying with well-adjusted ones. Participants’ mood assimilated to the standard: Participants reported more positive mood after having been exposed to the well-adjusted than the poorly-adjusted standard. Anxiety and depression varied with the type of comparison process: It was lower the more they avoided unfavourable comparisons (contrasting with the well-adjusted patient and identifying with the poorly-adjusted one). Conclusions: Patients adjust their comparison processes to the standard to experience favourable comparisons. Especially avoiding unfavourable comparison processes reduces the risk of negative consequences after encountering other patients. Thus, patients may profit from comparisons as long as they engage in the right process.